Gastric histopathology, iron status and iron deficiency anemia in children with Helicobacter pylori infection - ERTEM ŞAHİNOĞLU, DENİZ (LIPPINCOTT WILLIAMS & WILKINS, 2004)
Objectives: Helicobacter pylori has been established as a major cause of gastritis and peptic ulcer disease in adults and children. H. pylori infection may also have a role in the development of some extragastrointestinal diseases, including iron deficiency anemia. The aim of this study is to investigate H. pylori-related changes in gastric physiology and histology and the relationship of these changes to iron deficiency anemia in children. Methods: Fifty-two patients with gastrointestinal complaints were studied. Hematologic parameters, 3-day vitamin C and iron consumption, serum gastrin levels, and gastric juice ascorbic acid levels were compared in patients with and without H. pylori infection. Dietary intake of vitamin C and iron, serum gastrin, gastric juice ascorbic acid content, and gastric histology were compared in patients with H. pylori infection and anemia and in patients with H pylori infection and no anemia. The CagA status of the H. pylori organisms was evaluated. Results: Twenty-eight of 52 patients had H. pylori. Thirty-one patients had iron deficiency anemia. H. pylori infection was associated with low serum iron levels. H. pylori gastritis was associated with a decrease in the gastric juice ascorbic acid level. Infection with CagA-positive strains was associated with a greater decrease in gastric juice ascorbic acid than infection with CagA-negative strains. However, the gastric juice ascorbic acid levels of patients with H. pylori and anemia were not different from those of non-anemic patients with H. pylori. Among patients with H. pylori infection, pangastritis was twice as common in those with anemia than in those without anemia. Conclusions: H. pylori infection was associated with a decrease in gastric juice ascorbic acid concentration, and this effect was more pronounced in patients with the CagA-positive strain. Pangastritis was more common in patients whose H. pylori.infection was accompanied by anemia.
Keywords: Ascorbic acid; CagA; children; Helicobacter pylori; iron deficiency anemia; SIDEROPENIC REFRACTORY-ANEMIA; JUICE ASCORBIC-ACID; VITAMIN-C LEVELS; SERUM FERRITIN; ERADICATION; SECRETION; REVERSAL; ADULTS